Penerbitan Hak Guna Bangunan oleh Badan Hukum Pengembang Tanpa Akta Pelepasan Hak atas Tanah: Tinjauan terhadap Asas Kepastian Hukum - Rizki Wahyudi (Journal of Innovative and Creativity, 2025)
The study purpose was to examine the legal validity of the transition from Freehold Title to Building Rights Title in housing development projects, particularly when developers physically control the land but have not obtained juridical control due to the absence of a Land Rights Release Act. This study also aimed to analyze how this situation affects the principle of legal certainty under Indonesian national land law. The issue arises because Article 106 Section c of Law No. 1 of 2011 defines land rights transition as a sale-and-purchase process conducted only with parties who meet the requirements as legal holders of land rights. When such requirements are not met, the law mandates a land rights release by the holder to the state, which must then be followed by appropriate administrative procedures. Materials and methods. This study used a normative juridical approach by examining literature sources and secondary data consisting of primary, secondary, and tertiary legal materials, including statutory regulations, doctrinal writings, and relevant administrative practices. A field study was also used to support the juridical analysis and understanding of practical issues faced in housing development transactions. Results. Findings indicate that the transition of unregistered land intended for housing development must be carried out through a Land Rights Release Act executed before a notary. This mechanism functions as an exception within the framework of national land law and differs from the usual authority granted to Land Deed Officials. The absence of such an act causes defects in the formal and administrative requirements for issuing Building Rights Title certificates. Conclusions. Building Rights Title issued without a Land Rights Release Act is considered administratively defective, leading to potential cancellation. Such cancellation may be requested from the Ministry of Agrarian Affairs and Spatial Planning or the Head of the Land Office.